A Proposal to Exploit Legal Term Repertoires Extracted Automatically from a Legal English Corpus - Marín Pérez, María José (Miscelánea: A Journal of English and American Studies, 2014)
The use of specialised corpora as support material in ESP/EAP is a widespread phenomenon yet, to the best of our knowledge, the amount of corpus-based materials in the area of legal English is considerably reduced. This study presents the proposal of several corpus-based activities to foster the acquisition of legal terminology. To that end, an 8.85 million-word legal English corpus (BLaRC) was compiled and processed to identify its most relevant terms using P.Drouin's (2003) TermoStat software. A corpus comprising three legal English textbooks (LegTeXT) was created to establish a comparison between the term inventories obtained from both corpora and thus determine the usefulness of the term list obtained from the former corpus to be used as support teaching material. Several tests were carried out finding 67% overlap between the two term inventories. Furthermore, using Heatley and Nation's (1996) Range software, it was found that 12.37% of the running words in the legal English textbooks were covered by the term inventory obtained from BLaRC. After reviewing the literature on the subject, a taxonomy is also suggested for the classification of legal terms followed by the proposal of several vocabulary activities focusing on varied linguistic levels, namely, morphological, syntactic, semantic and discursive.
Keywords: Specialised corpora; English for specialised purposes (ESP); datadriven learning (DDL); legal English